2008
DOI: 10.1007/s00586-007-0577-6
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of sick-leave and health outcomes in injured workers with back pain

Abstract: Little is known about the sick-leave experiences of workers who make a workers' compensation claim for back pain. Our objective is to describe the 1-year patterns of sick-leave and the health outcomes of a cohort of workers who make a workers' compensation claim for back pain. We studied a cohort of 1,831 workers from five large US firms who made incident workers' compensation claims for back pain between January 1, 1999 and June 30, 2002. Injured workers were interviewed 1 month (n = 1,321), 6 months (n = 810… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 34 publications
1
16
0
1
Order By: Relevance
“…Pain-related disability in chronic low back pain patients varies between 11 % and 76 % [45,46] and this great variation is due to the disability concepts adopted as well as the different methods used to measure this phenomenon. In the present study, one-third to one-half of all nurses with low back pain showed difficulty in one or more of their activities of daily living, in the form of difficulty in sleeping (33.3 %), getting out of bed (30.4 %), standing up (39.9 %), walking (42.8 %), climbing stairs (50.7 %) and wearing clothes (20.3 %).…”
Section: Consequences Of Lbpmentioning
confidence: 99%
“…Pain-related disability in chronic low back pain patients varies between 11 % and 76 % [45,46] and this great variation is due to the disability concepts adopted as well as the different methods used to measure this phenomenon. In the present study, one-third to one-half of all nurses with low back pain showed difficulty in one or more of their activities of daily living, in the form of difficulty in sleeping (33.3 %), getting out of bed (30.4 %), standing up (39.9 %), walking (42.8 %), climbing stairs (50.7 %) and wearing clothes (20.3 %).…”
Section: Consequences Of Lbpmentioning
confidence: 99%
“…Disability in chronic low back pain patients varies between 11% and 76% (5)(6) and this great variation is due to the disability concepts adopted as well as the different methods used to measure this phenomenon. This variation makes comparisons among studies difficult.…”
Section: Descriptoresmentioning
confidence: 99%
“…A study conducted in North America found that women treated for breast cancer missed an average of 44.5 days from work within the first 6 months following diagnosis; the median days missed was 22 [20]. Length of work absence is important because sickness absence is a risk factor for permanently leaving the workforce [21]. A survey of 267 cancer survivors (48% were breast cancer survivors) in England found that the length of sick leave was significantly related to return to work within 18 months of cancer diagnosis [odds ratio 1.68, 95% confidence interval (CI) 1.23-2.28] [22].…”
Section: Introductionmentioning
confidence: 99%